Influence of Inspirational Motivation on Implementation of Human Resource Management Policies by Kakamega County Government, Kenya - Okoth, Okoth Bonface (Journal of Resources Development and Management, 2021)
This study aimed to establish the influence of inspirational motivation on implementation of Human Resource Management policies by County Government of Kakamega. A descriptive research design and sample survey method involving use of questionnaire as the primary data collection instrument was adopted. The study population was 6,328 County Government of Kakamega employees. Simple random sampling technique was applied to get a sample size of 154 respondents with a pilot study being conducted in Bungoma County where the study checked for internal consistency and reliability of the instrument for data collection. Cronbach’s coefficient alpha of 0.867 was obtained for internal reliability. Ethics governing research were accorded utmost consideration. A 92.7% return rate was attained, good for social statistics analysis. The Statistical Package for the Social Sciences (SPSS) was used to analyze data in the study. Pearson Product Moment Correlation Coefficient and linear regression were used in analysis within 95% confidence interval to test for associations, relationships and independence of indicators. Study findings revealed a significant and positive relationship between inspirational motivation and implementation of Human Resource Management Policies. Based on the study findings, it was concluded that inspirational motivation as a construct of transformational leadership had a significant positive influence on implementation of Human Resource Management policies at Kakamega County Government. The study therefore stretches the frontiers of knowledge on the nexus between transformational leadership and implementation of Human Resource Management policies and recommends the adoption of Human Resource Management practices that harness the benefits of transformational leadership at the work places not only at the County Government of Kakamega but in all public and private organizations in Kenya and beyond.
Keywords: Idealized Influence; Implementation; uman Resource Management Policies